2010
DOI: 10.1016/j.jacc.2009.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Implantation for Stenosed and Regurgitant Aortic Valve Bioprostheses

Abstract: Transcatheter aortic valve implantation is increasingly being used to treat severe aortic stenosis in patients with high operative risk. In an aging population the incidence of aortic stenosis is rising, and increasing numbers of elderly patients are undergoing aortic valve replacement with bioprosthetic valves. Therefore, there is a corresponding increase in prosthetic degeneration. This presents cardiologists with a cohort of patients for whom the risk of re-do aortic valve surgery is prohibitive. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 17 publications
0
53
0
1
Order By: Relevance
“…8 -10 In recent years, several reports have suggested that the off-label use of TAVR within failed surgically inserted bioprosthetic valves (valve-in-valve [VIV]) is technically feasible. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] However, all previous reports evaluating the VIV approach have included a small number of cases and are limited in providing measures of efficacy and safety. High postprocedural gradients and several potentially life-threatening complications, such as ostial coronary obstruction, were only reported anecdotally, and there was no comparison between different devices possibly applicable for VIV.…”
Section: Editorial See P 2280 Clinical Perspective On P 2344mentioning
confidence: 99%
“…8 -10 In recent years, several reports have suggested that the off-label use of TAVR within failed surgically inserted bioprosthetic valves (valve-in-valve [VIV]) is technically feasible. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] However, all previous reports evaluating the VIV approach have included a small number of cases and are limited in providing measures of efficacy and safety. High postprocedural gradients and several potentially life-threatening complications, such as ostial coronary obstruction, were only reported anecdotally, and there was no comparison between different devices possibly applicable for VIV.…”
Section: Editorial See P 2280 Clinical Perspective On P 2344mentioning
confidence: 99%
“…7,[20][21][22] A Canadian registry (n=24) was soon followed by an Italian registry (n=25), 2 German registries (n=20, n=47), and numerous other small case series and isolated case reports documenting favorable outcomes. 7,8,[23][24][25][26][27][28][29][30][31] The Global Valve-in-Valve Registry, an industry-independent collaboration, was introduced in 2010 to collate this increasing but widely distributed experience.…”
Section: The Vinv Procedures Clinical Experiencementioning
confidence: 99%
“…Typically, transapical access is preferred for VIV procedures, although reports have recently emerged describing the transaxillary and trans-subclavian approaches (Olsen et al, 2010). The Edwards SAPIEN valve may be better suited to VIV implantation (Kempfert et al, 2010), although the Medtronic CoreValve system has been successfully used (Khawaja et al, 2010). There are promising early results for VIV, although reports tend to be anecdotal or restricted to small case series, and no large comparative studies are currently available (Ferrari et al, 2010;Kempfert et al, 2010;Khawaja et al, 2010;Olsen et al, 2010;Sharp et al, 2010).…”
Section: Expanding the Role Of Tavimentioning
confidence: 99%
“…The Edwards SAPIEN valve may be better suited to VIV implantation (Kempfert et al, 2010), although the Medtronic CoreValve system has been successfully used (Khawaja et al, 2010). There are promising early results for VIV, although reports tend to be anecdotal or restricted to small case series, and no large comparative studies are currently available (Ferrari et al, 2010;Kempfert et al, 2010;Khawaja et al, 2010;Olsen et al, 2010;Sharp et al, 2010). Transvalvular gradients post-procedure are usually satisfactory (Ferrari et al, 2010;Kempfert et al, 2010;Walther et al, 2008a), while residual aortic regurgitation tends to be minimal (Kempfert et al, 2010).…”
Section: Expanding the Role Of Tavimentioning
confidence: 99%